Technique for inguino‐femoral lymph node dissection in vulvar cancer: an international survey. Issue 6 (June 2021) - Jones, Sadie Esme Fleur; Ramirez, Pedro T; Bhandoria, Geetu Prakash; Hsu, Heng‐Cheng; Nair, Navya; Noll, Florencia; Hurt, Christopher N; Howells, Robert; Lim, Kenneth; Sharma, Aarti
ABSTRACT : Background : Vulvar cancer is a rare disease and despite broad adoption of sentinel lymph node mapping to assess groin metastases, inguino‐femoral lymph node dissection still plays a role in the management of this disease. Inguino‐femoral lymph node dissection is associated with high morbidity, and limited research exists to guide the best surgical approach. Objective : To determine international practice patterns in key aspects of the inguino‐femoral lymph node dissection technique and provide data to guide future research. Methods : A survey addressing six key domains of practice patterns in performing inguino‐femoral lymph node dissection was distributed internationally to gynecologic oncology surgeons between April and October 2020. The survey was distributed using the British Gynecological Cancer Society, the Society of Gynecologic Oncology, authors' direct links, the UK Audit and Research in Gynecology Oncology group, and Twitter. Results : A total of 259 responses were received from 18 countries. The majority (236/259, 91.1%) of respondents reported performing a modified oblique incision, routinely dissecting the superficial and deep inguino‐femoral lymph nodes (137/185, 74.1%) with sparing of the saphenous vein (227/258, 88%). Most respondents did not routinely use compression dressings/underwear (169/252 (67.1%), used prophylactic antibiotics at the time of surgery only (167/257, 65%), and closed the skin with sutures (192 74.4%). Also, a drain is placed at the time of surgery by 243/259 (93.8%) surgeons, with most practitioners (144/243, 59.3%) waiting for drainage to be less than 30‐50 mL in 24 hours before removal; most respondents (66.3%) routinely discharge patients with drain(s) in situ. Conclusion : Our study showed that most surgeons perform a modified oblique incision, dissect the superficial and deep inguino‐femoral lymph nodes, and spare the saphenous vein when performing groin lymphadenectomy. This survey has demonstrated significant variability in inguino‐femoral lymph node dissection in cases of vulvar cancer among gynecologic oncology surgeons internationally.